Revive la historia en la residencial San Felipe - Aquije Zegarra, Daniela (2024)
Revive history is a persuasive proposal whose main objective is to reconnect the inhabitants of Residencial San Felipe with the history of this architectural complex through the elaboration of printed, digital and three-dimensional graphic pieces. Under the slogan of “reunion” as a social interaction, the residents will rediscover the history of the residence after a long period of confinement due to the COVID-19 pandemic. Consequently, as part of this proposal, the development of various digital and printed graphic pieces has been proposed, as well as the use of three-dimensional spaces for social interaction under explosion in two public spaces of the residence: the La Alameda Belaunde Terry and el Centro Bancario, also called la Plaza Principal. These spaces were chosen on the basis of ethnographic and psychographic research, heat maps, interviews with professionals and verifications of relevant bibliographic sources. In the same way, the target user is delimited based on his generational technological knowledge and his social skills: from six-year-old children to adults over sixty. For this reason, a specific communicative role has been given to each piece in order to fulfill the main objective.